Interplate Slip Following the 2003 Tokachi‐oki Earthquake From Ocean Bottom Pressure Gauge and Land GNSS Data. Issue 4 (23rd April 2019) - Itoh, Yuji; Nishimura, Takuya; Ariyoshi, Keisuke; Matsumoto, Hiroyuki
Abstract: Preseismic, coseismic, and 7.5 years of postseismic deformation of the 2003 M w 8.0 Tokachi‐oki earthquake are modeled using land Global Navigation Satellite System (GNSS) data and two ocean bottom pressure gauges (OBP) using viscoelastic Green's functions. The postseismic slip distribution is shown to not overlap with the main shock or the source regions of past large earthquakes along the southern part of the Kurile trench. The preseismic locking is estimated in the coseismic and postseismic slip regions using the same plate interface geometry. The temporal evolution of the postseismic slip is described with a single logarithmic function. The slip is shown to decay faster updip of the coseismic slip region compared to the downdip extension. Sustained postseismic slip indicates that the interplate locking in the postseismic slip region had not fully recovered to the pre‐2003 status in the 7.5 year analyzed period. Postseismic slip history also indicates rapid recovery of locking in the coseismic slip region. We examined the constraint of the OBP time series for the postseismic deformation modeling and found that the observed uplift at the OBP sites requires small postseismic slip near the trench, where a tsunamigenic M 9 earthquake occurred in the seventeenth century. Uplift at the OBP sites does not constrain the absolute slip magnitude between the updip and downdip sides of the OBP sites but requires the slip in the updip side to be smaller than that in the downdip side. Our model describes transient postseismic deformation observed by both land GNSS and OBP. Key Points: Spatiotemporal postseismic slip of the 2003 Tokachi‐oki earthquake for ~7.5 years is estimated using land and seafloor geodetic data Interplate locking of postseismic slip region had not fully recovered to the pre‐2003 status after 7.5 years following the main shock Postseismic deformation could be responsible for transient seafloor pressure changes following the 2003 event